QUANTUM CHEMICAL STUDY FOR THE TOXICITY PREDICTION OF SULFONAMIDE ANTIBIOTICS WITH QUANTITATIVE STRUCTURE - ACTIVITY RELATIONSHIP - Aydogdu, S.; Hatipoglu, A. (PLAPIQUI(UNS-CONICET), 2021)
Sulfonamides are one of the most important classes of chemicals found in the aquatic environment, as a pollutant due to excessive consumption. The DFT-B3LYP method with the basis set 6-311++G (d,p), was employed to calculate various quantum chemical descriptors of sulfonamide molecules. A quantitative structure activity relationship (QSAR) study was performed for the toxicity value LD50 of sulfonamides, with their quantum chemical descriptors, by multi linear regression. The QSAR models were validated by internally and externally. The best multilinear equation with correlation coefficient, R, and the cross-validation leave-one-out correlation coefficient, Q(2), values were 0.9528 and 0.8556, respectively The results show that the QSAR models have both favourable estimation stability and good prediction power.
Keywords: DFT; sulfonamides; quantum chemical descriptors; multi linear regression; MIXTURE TOXICITY; PHOTOCATALYTIC DEGRADATION; TRANSFORMATION PRODUCTS; MECHANISM; VALIDATION; Engineering